MODEL AND SIMULATION OF 3D DAM BREAK BASED ON SMOOTHED PARTICLE HYDRODYNAMICS (SPH) - TRISNAWAN PUTRA (NIM : 20910003); Pembimbing : Dr. Suprijadi, M.Eng., ANGGYI
Smoothed particle hydrodynamics (SPH), is a particle method which, at very beginning, only applied on astrophysical phenomenon simulation. SPH spread widely, it can compete with other numerical method for solving Navier-Stokes formula, that is the key of fluid simulation, and produce realistic simulation. Therefore, SPH is widely developed in the film industry and video game production for creating required effects. In this thesis, SPH is developed for supporting solid particle in use for simulation. Solid particle is treated same as fluid particle, with little calculation addition in the end, for converting gained position become translation and rotation of the solid object in a whole body. With this capability, the result of 3D dam break simulation can be varies and interesting. The goal of the research of this thesis is for collecting data of fluid and solid particle interaction results, by doing two scenarios. The first scenario executed several times with different height of the fluid, then the data of distance traveled by the sliding of solid objects through the effect of the fluid is taken. Obtained the conclusion that the higher the fluid, then the sliding distance of solid objects farther away. In the second scenario, simulation executed with varied height of the solid object, then time data needed by fluid for taking the solid object down. The conclusion is the higher the solid object, then the longer it takes the fluid to knock it down.